2013
DOI: 10.1016/j.cell.2013.10.057
|View full text |Cite|
|
Sign up to set email alerts
|

miR-9a Minimizes the Phenotypic Impact of Genomic Diversity by Buffering a Transcription Factor

Abstract: Gene expression has to withstand stochastic, environmental and genomic perturbations. For example, in the latter case, 0.5–1% of the human genome is typically variable between any two unrelated individuals. Such diversity might create problematic variability in the activity of gene regulatory networks, and ultimately, in cell behaviors. Using multigenerational selection experiments, we find that for the Drosophila proneural network, the effect of genomic diversity is dampened by miR-9a-mediated regulation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 62 publications
2
112
0
Order By: Relevance
“…Yet the miR-7 mutation affected both the mean and variance of the cell fate phenotype 115 . Similarly, miR-9a-mediated regulation of the transcription factor senseless (sens) is important to stabilize bristle number in the Drosophila melanogaster scutellum upon natural genetic variation, and miR-9a mutations affect both phenotypic variance and mean 116 . Therefore, strictly speaking, it is unclear whether mi RNAs evolved to confer developmental robustness.…”
Section: Phenotypic Capacitorsmentioning
confidence: 99%
“…Yet the miR-7 mutation affected both the mean and variance of the cell fate phenotype 115 . Similarly, miR-9a-mediated regulation of the transcription factor senseless (sens) is important to stabilize bristle number in the Drosophila melanogaster scutellum upon natural genetic variation, and miR-9a mutations affect both phenotypic variance and mean 116 . Therefore, strictly speaking, it is unclear whether mi RNAs evolved to confer developmental robustness.…”
Section: Phenotypic Capacitorsmentioning
confidence: 99%
“…Sens is a direct target of miR-9 , and in the absence of this miRNA about 33% of larvae develop extra sensory organs [98], presumably because fluctuations in Sens levels inappropriately trigger ectopic cell fate decisions [99]. Interestingly, recent experiments suggest that miR-9 can also minimize the impact of genomic diversity on sensory organ differentiation, thus providing an example of genetic buffering by a miRNA [100]. …”
Section: Mechanisms Of Canalization By Mirnasmentioning
confidence: 99%
“…Microbiologists 5,6 , geneticists 7,8 , biochemists 9-11 , and population geneticists 12,13 found that experimental evolution, in which replicate populations of diverse model organisms are allowed to adapt to novel but controlled laboratory environments (Figure 1), could shed new light on the biological processes they studied. For a long time the different fields focused either on the dynamics of adaptation and/or on the phenotypic or physiological impact on organisms, rather than on the underlying genetic changes that were not easily accessible.…”
Section: Introductionmentioning
confidence: 99%